As you like it - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
Rosalind, daughter of the deposed Duke Senior, is exiled from the court by her wicked uncle. Disguising herself as a young man and accompanied by her cousin Celia and their loyal fool Touchstone, she takes refuge in the Forest of Arden. In the forest Rosalind meets young Orlando with whom she is in love, but her male disguise complicates matters, especially when Rosalind finds she has unwittingly attracted the shepherdess Phebe.
Keywords: Fathers and daughters -- Drama; Exiles -- Drama